The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
General, Applied and Systems Toxicology 2009
DOI: 10.1002/9780470744307.gat150
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxins with a Special Focus on Aflatoxins, Ochratoxins and Fumonisins

Abstract: Mycotoxins are important environmental and carcinogenic agents. They are ubiquitous in a broad range of commodities and cause toxic responses when ingested by humans and animals. A review of mycotoxins is presented with special reference to the producing species, analytical methodology, occurrence, biological activity, decontamination, regulations and the risk assessment of aflatoxins, ochratoxins and fumonisins. Some of the most recent studies regarding the mechanisms involved in fumonisin B 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 544 publications
0
4
0
1
Order By: Relevance
“…Optimum conditions are 16-24 % moisture at 20-38 ºC. However, it is reported that aflatoxins production can also take place at temperatures as low as 7-12 ºC 17 . After harvest, if grains are not dried quickly or during storage remains at moisture high enough, mycotoxins such as aflatoxins may Aflatoxins contamination in foods, which causes the economic loss and threats to public health, is a world wide problem encountered from time to time in most countries of the world.…”
Section: Resultsmentioning
confidence: 99%
“…Optimum conditions are 16-24 % moisture at 20-38 ºC. However, it is reported that aflatoxins production can also take place at temperatures as low as 7-12 ºC 17 . After harvest, if grains are not dried quickly or during storage remains at moisture high enough, mycotoxins such as aflatoxins may Aflatoxins contamination in foods, which causes the economic loss and threats to public health, is a world wide problem encountered from time to time in most countries of the world.…”
Section: Resultsmentioning
confidence: 99%
“…Optimum conditions are 16-24% moisture at 20-38°C. However, it is reported that AF production can also take place at temperatures as low as 7-12°C (Steyn & Stander, 2000). After harvest, if grain is not dried quickly or during storage remains at a moisture high enough, mycotoxins such as AFs may occur.…”
Section: Resultsmentioning
confidence: 99%
“…In ruminants, protozoa and bacterial enzymes in the anterior stomach hydrolyze OA, resulting in phenylalanine and non-toxic OTα formation (Battacone et al, 2010;Mobashar et al, 2012). However, enzymes involved in the metabolism of phenylalanine indirectly have adverse effects on lipid peroxidation and mitochondrial respiration (Steyn & Stander, 1999).…”
Section: Discussionmentioning
confidence: 99%